Barbosa, G. (2022). The Best of Hard Times: Palestinian Refugee Masculinities in Lebanon. Syracuse, New York: Syracuse University Press. - Oliveira, Rafael Gustavo de (Campos - Revista de Antropologia, 2022)
Resenha do livro The Best of Hard Times: Palestinian Refugee Masculinities in Lebanon, de Gustavo Barbosa, publicado em 2022.